Big Data Usage Intentionusing Toe Framework: Sri Lankan Context - Haleem, Athambawa (The journal of contemporary issues in business and government, 2021)
Big data is huge amount of information that cannot be handled with conventional method.In various fields, the field of big data has an essential role to play.This research investigated that the Big Data Usage Intention of listed companies in Sri Lanka, is to provide empirical evidence concerning the Big Data Usage Intention of listed companies. Data were collected using survey and market research techniques in listed companies in CSE. For this purpose, descriptive, correlation, and multiple regression analysis was employed. In many fields of business and management, Big Data Analysis (BDA) is an emerging technology. Factors affecting the organizational intention to use this technology do not focus on extensive research. In order to fully exploit its advantages and therefore to study it, organizations should take it in a full and profound level. This research, based on the TOE, proposes and examines the determinants which influence the adoption of the BDA in the context of companies from Sri Lanka. There is large collection of data from 96 organizations, which helps us to understand the influences on the use of big data.